The Effect of Security Perception, Financial Literacy and Content Marketing on Mutual Fund Purchase Decisions on The Bibit Application with Trust As A Mediation - I Gede Wisnu Satria Chandra Putra; Shirleen Alysia Valencia (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2025)
These instructions give you basic guidelines for preparing papers for the IConEnt 2023. Papers must be submitted using this format. This document is a template for Microsoft Word. If you are reading a paper version of this document, please download the electronic file from the Conference website so you can use it to prepare your manuscript. Abstract should not exceed 180 words. Please include appropriate key words in your abstract, in alphabetical order, separated by commas.